Mass and Popular Culture: Problem of Demarcation - Тaras Lyuty (Наукові записки НаУКМА: Філософія та релігієзнавство, 2019)
This article is an attempt to examine the differences between mass and popular culture in the historical and sociocultural dimensions. The author traces the relations of these two phenomena to the general sphere of culture and its main principles. The key point of the article is that culture is a kind of arrangement, cultivation, education, and perfection. On the other hand, manifestations of mass culture are associated with the decline of its sublime foundations. Therefore, there is a necessity to compare the ‘high’ and ‘low’ levels of culture. The rise of commercial activity and the common consumption became the turn point of the emergence of a non-elite level of culture. Industrialization and urbanization accelerated the development of mass media, which helped bring the goods of civilization to the majority of people. Due to market mechanisms, the spread of wealth took place under the dictates of commercial success. Artistic and aesthetic parameters of culture did not fit into the pragmatic requirements, and marketing programs of mass production weakened those parameters. Wide-ranging conformism, infantilism, and consumerism were increasing. These trends are well known as mass culture. The indicator of this condition of culture is simplification of tastes. At the same time, there was a popular traditional lower culture, the main features of which were accessibility and commonness, and it had an unofficial and peripheral status. However, these two formations (elite and popular culture) did not enter into rigid antagonism. The author is analyzing the development of a popular culture from the ancient to the modern times. It is concluded that culture not only creates high ideals but also may be limited to simpler meanings. The author shows that the popular culture also opposes mass culture due to creation of alternative forms of resistance. It means that popular culture has not completely collapsed into conformism but kept the protest intention. Thanks to this alternative particularity, pop-culture has gradually become significantly different from masscult. It allows for grasping distinctions between these two kinds of culture. Finally, popular culture remains the domain of the formation of ideas in which social players express the values of their everyday life.